2005
DOI: 10.1016/j.chembiol.2005.08.008
|View full text |Cite
|
Sign up to set email alerts
|

A Proteome-Wide CDK/CRK-Specific Kinase Inhibitor Promotes Tumor Cell Death in the Absence of Cell Cycle Progression

Abstract: The identification of molecular determinants of tumor cell survival is an important objective in cancer research. Here, we describe a small-molecule kinase inhibitor (RGB-286147), which, besides inhibiting tumor cell cycle progression, exhibits potent cytotoxic activity toward noncycling tumor cells, but not nontransformed quiescent fibroblasts. Extensive yeast three-hybrid (Y3H)-based proteome/kinome scanning with chemical dimerizers revealed CDK1/2/3/5/7/9 and the less well-characterized CDK-related kinases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 52 publications
0
36
2
Order By: Relevance
“…CCRK was identified in a large-scale small interfering RNA (siRNA) screen for suppressors of apoptosis (36). A specific chemical inhibitor of CDK family members (RGB-286147) inhibits CCRK and promotes apoptosis in the absence of cell cycle progression (6). This is intriguing because it supports structural similarity of CCRK to other CDKs (35), but the target(s) for RGB-286147 that promotes apoptosis is unknown.…”
Section: Discussionmentioning
confidence: 91%
“…CCRK was identified in a large-scale small interfering RNA (siRNA) screen for suppressors of apoptosis (36). A specific chemical inhibitor of CDK family members (RGB-286147) inhibits CCRK and promotes apoptosis in the absence of cell cycle progression (6). This is intriguing because it supports structural similarity of CCRK to other CDKs (35), but the target(s) for RGB-286147 that promotes apoptosis is unknown.…”
Section: Discussionmentioning
confidence: 91%
“…Genomic profile by DNA microarrays in that model revealed the down-regulation of the cell cycle-related kinase (CCRK) after development of HF. Although this protein has not been characterized in the heart before, it is known that CCRK plays a major role in promoting the growth of cancer cells (7). Therefore, the goal of the present study is to characterize the expression of CCRK in the normal and failing heart and to determine whether this kinase is involved in cardiac mechanisms of cell growth and survival.…”
mentioning
confidence: 99%
“…Cells lacking CCRK were incapable of growth, whereas cells with a reduced level of CCRK grew at a significantly slower rate than control cells (7,16). Most interestingly, it was shown that a specific inhibition of CCRK promotes tumor cell death (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Roscovitine and CDK9 Inhibitor II (4-(3,5-diamino-1H-pyrazol-4-ylazo)-phenol) inhibited tracer binding weakly, with K i values >10 µM. CDK/CRK inhibitor (RGB-286147) inhibited with a K i near 120 nM, which is within the range of IC 50 values seen for a variety of CDKs with this inhibitor, 32 and CDK2/9 inhibitor ((4-(2-Amino-4-methylthiazol-5-yl)pyrimidin-2-yl)-(3-nitrophenyl)amine) demonstrated a K i of 72 nM, also within the range of potencies seen for this inhibitor with other CDKs. 33 The adenosine mimetic 5-iodotubercidin and the broad-spectrum kinase inhi bitor staurosporine bound tightest, with K i values of 23 nM and 2.8 nM, respectively.…”
Section: Characterization Of Compounds That Bind To Cdksmentioning
confidence: 74%